Islamismus in der Jugendphase Eine rekonstruktive Studie zu Radikalisierungsprozessen - Frank, Anja (Rekonstruktive Forschung in der Sozialen Arbeit, 2023)
How do young people find their way into Islamist contexts and towards Islamist positions? The authors conducted biographical-narrative interviews with young people, who held different positions in this field of ideological positions. They look at the actual forms and features of the particular worldviews and processes of (de-)radicalisation and show how individual notions of the self and the world are intertwined with social interaction within families, peergroups, radical groups, or official institutions.